The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1753-0407.12569
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM3 content in skeletal muscles is increased in type 2 but decreased in type 1 diabetes rat models: Implications of glycosphingolipid metabolism in pathophysiology of diabetes

Abstract: The expression patterns of GM3 ganglioside and its precursors in diabetic rats suggest that the role of glycosphingolipid metabolism may differ between T2DM and T1DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Rats fed a high-fat, obesogenic diet for 12 weeks had an accumulation of hexosylceramides in adipose tissue but a depletion in muscle (27). However, in rodent diabetes models, it was found that muscle hexosylceramide levels increased in a T2DM model but decreased in a T1DM model (28). In the current study, we identified only 1 GM3 species (d18:1/16:0).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 43%
“…Rats fed a high-fat, obesogenic diet for 12 weeks had an accumulation of hexosylceramides in adipose tissue but a depletion in muscle (27). However, in rodent diabetes models, it was found that muscle hexosylceramide levels increased in a T2DM model but decreased in a T1DM model (28). In the current study, we identified only 1 GM3 species (d18:1/16:0).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 43%
“…Thus, incorporating HFD and STZ simulates not only the phenotype, but also the pathogenesis of human T2DM. This has made it a widely recognized method for induction of T2DM in rats (Reed et al, 2000;Flanagan et al, 2008; Liu et al, 2015;Bozic et al, 2018). By feeding an HFD for four weeks and administering STZ at a dose of 35 mg/kg, we successfully created a T2DM model in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, decreased plasma levels of very long-chain ceramide were associated with a significantly lower frequency of developing diabetes-related nephropathy and macroalbuminuria. Moreover, the reduction of sphingolipids containing fatty acid C24:1 was demonstrated and associated with a reduction in cardio-and neuro-protection [7,9].…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…The role of S1P in inflammation and pathogenesis is not easy to understand. Autoimmune diabetes and especially its complications were associated with a dysmetabolism in the sphingolipids [7,9]. In particular, decreased plasma levels of very long-chain ceramide were associated with a significantly lower frequency of developing diabetes-related nephropathy and macroalbuminuria.…”
Section: Type 1 Diabetesmentioning
confidence: 99%